Analisis Hasil Belajar IPA Materi Organ Gerak Hewan dan Manusia pada Siswa Kelas V SD Negeri 07 Martapura - Sonia, Mita; Sukardi, Sukardi; Surmilasari, Nora (Indonesian Research Journal on Education, 2022)
The purpose of this study was to find out how the science learning of organ material on animalmovement and movement in humans in V grade students of SD Negeri 07 Martapura. The method used is descriptive qualitative method. The results of the study are based on the results of research data analysis, that the learning outcomes of science learning material for animal and human movement organs in V grade students of SD Negeri 07 Martapura are still low. On the indicator of understanding and understanding the movement organs of animals and humans set the total score of 50 with a low percentage of 55%, on the indicator mentioning the organs of motion in animals and humans set a total score of 70 with a percentage of 15% high, the indicator mentions of each animal and human movement organ with a score of 56 percentage 30% moderate, the indicator is able to explain the locomotor organs and their functions in animals and humans clearly and smoothly with a total score of 46 percentage 55% low and the indicator is able to explain how maintain the health of locomotor organs in humans with a total score of 46 percentage 55% low.